RECUPERATING FAITH FROM DESPAIR IN HELEAN GARNER’S THE CHILDREN BACH (International Journal of Food and Nutritional Sciences, 2022)
While Literature is the physique, faith is the spirit that is confronted in the practice of Psychoanalysis. A lack of self-confidence or the loss of faith is linked to despair and a consequent display of aggressiveness. In psychoanalysis, Faith develops quickly and is the result of a great deal of effort put forward within relationships. This paper explores the theme of resilience as depicted via the character of Dexter, who navigates the challenges within his marriage and ultimately overcomes various obstacles alongside Credence